Propelling the innovation speed for Malaysian biotechnology products - Farid, Hadi; Ismail, Ismi Arif; Sadeghi, Zahra; Rana, Md. Sohel (Marsland Press, 2013)
The aim of this paper is to examine the effect of professional expertise, managerial, markets related knowledge and experience on innovation speed of new product performance related to biotechnology companies. Innovation speed is considered as a core element in performance of new product. Many researchers have stated a positive and effective interaction between success of new product performance and speed to market. Another point is that innovation speed provides a firm and sustainable competitive advantage. And at last, innovation speed for each biotechnology company is valuable resource and tries to have close relationship between customers and their requirements. The innovation speed cannot be developed easily just by project managers, technological developments and competitors in all around the world; in many results of researches it can be seen that innovation speed has been absent in marketing strategies, especially in biotechnology companies. Bringing innovation speed in biotechnology companies to increase profit of the company is big challenge in marketplace.